Comparative Genomic Analysis of Three Salmonid Species Identifies Functional Candidate Genes Involved in Resistance to the Intracellular Bacterium Piscirickettsia salmonis - Yáñez, José M.; Yoshida, Grazyella M.; Parra, Ángel; Correa, Katharina; Barría, Agustín; Bassini, Liane N.; Christensen, Kris A.; López, Maria E.; Carvalheiro, Roberto; Lhorente, Jean P.; Pulgar, Rodrigo (Frontiers in Genetics, 2019)
Piscirickettsia salmonis is the etiological agent of Salmon Rickettsial Syndrome (SRS), and is responsible for considerable economic losses in salmon aquaculture. The bacteria affect coho salmon (CS) (Oncorhynchus kisutch), Atlantic salmon (AS) (Salmo salar) and rainbow trout (RT) (Oncorhynchus mykiss) in several countries, including: Norway, Canada, Scotland, Ireland and Chile. We used Bayesian genome-wide association (GWAS) analyses to investigate the genetic architecture of resistance to P. salmonis in farmed populations of these species. Resistance to SRS was defined as the number of days to death (DD) and as binary survival (BS). A total of 828 CS, 2,130 RT and 2,601 AS individuals were phenotyped and then genotyped using ddRAD sequencing, 57K SNP Affymetrix® Axiom® and 50K Affymetrix® Axiom® SNP panels, respectively. Both trait of SRS resistance in CS and RT, appeared to be under oligogenic control. In AS there was evidence of polygenic control of SRS resistance. To identify candidate genes associated with resistance, we applied a comparative genomics approach in which we systematically explored the complete set of genes adjacent to SNPs which explained more than 1% of the genetic variance of resistance in each salmonid species (533 genes in total). Thus, genes were classified based on the following criteria: i) shared function of their protein domains among species, ii) shared orthology among species, iii) proximity to the SNP explaining the highest proportion of the genetic variance and, iv) presence in more than one genomic region explaining more than 1% of the genetic variance within species. Our results allowed us to identify 120 candidate genes belonging to at least one of the four criteria described above. Of these, 21 of them were part of at least two of the criteria defined above and are suggested to be strong functional candidates influencing P. salmonis resistance. These genes are related to diverse biological processes, such as: kinase activity, GTP hydrolysis, helicase activity, lipid metabolism, cytoskeletal dynamics, inflammation and innate immune response, which seem essential in the host response against P. salmonis infection. These results provide fundamental knowledge on the potential functional genes underpinning resistance against P. salmonis in three salmonid species.